2018
DOI: 10.11591/ijere.v7i2.12597
|View full text |Cite
|
Sign up to set email alerts
|

Mediation Role of Locus of Control on the Relationship of Learned-helplessness and Academic Procrastination among College Students in Penang, Malaysia.

Abstract: <span lang="EN-US">This study aims to study the mediation role of locus of control on the impact of learned helplessness on students’ academic procrastination. Studies reported that more than 70% university students procrastinate, and one of the causes is the perception that one is vulnerable or helpless in finishing the procrastinate tasks. It was hypothesized that internal locus of control iLOC can reduce the effect if the learned helplessness (LH) on academic procrastination. Data was collected from 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
13
0
1
Order By: Relevance
“…Therefore, learned-helplessness significantly changes the strength of state selfesteem in reducing perceived depression; social media users persistently feel cyberbullied due to their high frequency of exposure to the derogatory comments or posts directed towards them, resulting in increased perceived cyber-victimization, which eventually reduce the adequacy of their state self-esteem, increase their learned-helplessness, which will subsequently increase perceived depression. This finding supports the study of Young et al [22] that social media users with adequate self-esteem who have not learned that they are helpless might even respond aggressively to those who attempted to victimize them. Moreover, the second supplementary analysis indicated that the prevalence of having perceived cybervictimization reducing state self-esteem is not less than 20%.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, learned-helplessness significantly changes the strength of state selfesteem in reducing perceived depression; social media users persistently feel cyberbullied due to their high frequency of exposure to the derogatory comments or posts directed towards them, resulting in increased perceived cyber-victimization, which eventually reduce the adequacy of their state self-esteem, increase their learned-helplessness, which will subsequently increase perceived depression. This finding supports the study of Young et al [22] that social media users with adequate self-esteem who have not learned that they are helpless might even respond aggressively to those who attempted to victimize them. Moreover, the second supplementary analysis indicated that the prevalence of having perceived cybervictimization reducing state self-esteem is not less than 20%.…”
Section: Discussionsupporting
confidence: 91%
“…A study among 1963 early teenagers in the United States indicated that less adequate self-esteem levels were found among the participants who were involved in cyber-victimization, both as offenders and as victims [50]. By pin-pointing inadequate self-esteem as the outcome, their study supplemented their previous one, which reported that cybervictimization contributes to negative emotional and psychological in general [22].…”
Section: State Self-esteem As a Mediatormentioning
confidence: 80%
See 1 more Smart Citation
“…External factors include a negative evaluation from others [39], and peer influence [40]. Although these factors are considered external, individuals need to see them in a certain way before developing procrastination behavior [41]. Social support is verbal or non-verbal information or advice, real assistance, and actions given by social intimacy or acquired due to the presence of others, and has an emotional and behavioral benefit to the recipient [42].…”
Section:  Issn: 2252-8822mentioning
confidence: 99%
“…LH was operationalized via the construct of self-motivation, and was measured using the Self-Motivation Scale (Dishman & Ickes, 1981). This scale utilizes several theoretical paradigms relevant in the research field of LH, including achievement motivation (De Castella, Byrne, & Covington, 2013), locus of control (Prihadi et al, 2018), and attribution theory (Harvey, Madison, Martinko, Crook, & Crook 2014). The scale includes 40 items measured on a 5-point Likert scale (1 = very much unlike me, 5 = very much like me); reversing final score is necessary.…”
Section: Methodsmentioning
confidence: 99%